(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2022)
We aim comprehend how Environmental Education has been represented, from the conceptions of a group of teachers from the Region of Caparaó Capixaba/ES. We seek to answer two questions: What are the teachers’ conceptions about Environmental Education? What relationships are established with teacher training and performance? For thats, we discuss it from 4 categories: Conceptions; Development spaces; Responsible professionals; and Curriculum. We identified understandings of Environmental Education as "training process" and "practice", being recognized as important to be developed in spaces and by professionals different, especially in school environments and by Environmental Teachers and Educators. Its interdisciplinary character is highlighted by the teachers, articulating to the different areas of knowledge that are part of the Basic Education curriculum. We conclude by the interdisciplinary, theoretical and practical character of Environmental Education, not being limited to professionals or specific spaces. However, school spaces are admitted in their potential to promote Environmental Education, as well as Teachers and Environmental Educators. In this sense, we sign to the importance and relevance of the theme in processes of teacher training and performance.